2016
DOI: 10.1149/2.0981606jes
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of LiPF6in High Energy Lithium-Ion Batteries Studied with Online Electrochemical Mass Spectrometry

Abstract: The chemical and electrochemical instabilities of LiPF 6 in carbonate electrolytes for Li-ion batteries were studied with online electrochemical mass spectrometry (OEMS). Decomposition of carbonate electrolytes based on LiPF 6 eventually results in the formation of POF 3 , which is readily detected and followed in situ during operation of Li-rich HE-NCM-based Li-ion cells. Electrode potentials above ∼4.2 V leads to carbonate solvent oxidation and presumably the formation of ROH species, which subsequently hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
187
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(209 citation statements)
references
References 44 publications
(134 reference statements)
21
187
0
1
Order By: Relevance
“…Neither O 2 nor CO 2 are expected to be reduced at the LFP potential. 57 Its potential was monitored in a T-cell with a Li reference-electrode to Table I. Estimation of the molar fraction and thickness of the spinel-like surface layer for Model A (lattice oxygen-derived CO 2 only above ≈4.6 V) and Model B (CO 2 evolved prior to O 2 evolution at ≈4.6 V also due to the reaction with lattice oxygen), based on the gas evolution for the HE-NCM/Li cell data in Figure 3 (black lines).…”
Section: Ammentioning
confidence: 99%
“…Neither O 2 nor CO 2 are expected to be reduced at the LFP potential. 57 Its potential was monitored in a T-cell with a Li reference-electrode to Table I. Estimation of the molar fraction and thickness of the spinel-like surface layer for Model A (lattice oxygen-derived CO 2 only above ≈4.6 V) and Model B (CO 2 evolved prior to O 2 evolution at ≈4.6 V also due to the reaction with lattice oxygen), based on the gas evolution for the HE-NCM/Li cell data in Figure 3 (black lines).…”
Section: Ammentioning
confidence: 99%
“…19,20 At first sight, this seemed consistent with the mass spectrometrically detected O 2 and CO 2 evolution starting during the activation plateau, which was interpreted to indicate the release of Li 2 O from the bulk of the material during activation and accompanying structural changes within the bulk material. 15,17,18,23,24 However, the exact quantification of the released oxygen by Strehle et al and Luo et al revealed that the amount of released oxygen is an order of magnitude too low to be consistent with the assumed electrochemical oxygen release 25,26 and also that the O 2 evolution does not start until right after the activation plateau (only <10 μmol O2 /g AM during the plateau, but >100 μmol O2 /g AM following thereafter; shown by Strehle et al). 25 Both observations suggested that the observed oxygen release cannot be ascribed to a loss of oxygen from the bulk of the material, but that the oxygen is only being released from the near-surface Thus, more recent studies propose that bulk and surface of these overlithiated materials show distinctly different properties, rationalized by a bulk-shell model.…”
mentioning
confidence: 97%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20] These instruments are costly, and these methods require the preparation and measurement of many calibration solutions. Often the columns or detectors used in chromatography experiments cannot be exposed to the high temperature decomposition products of LiPF 6 , so these experiments often focus on the organic portions of the electrolyte, after the water-soluble portions of the electrolyte have been removed.…”
mentioning
confidence: 99%